Contribution of Interpersonal Communication and Work Motivation to Teacher Job Satisfaction at SMKN Bintan Regency, Riau Islands - Teddy Roberto; Yahya; Syahril; Anisah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Based on the survey in the field, it is shown that the job satisfaction of teachers at SMKN Bintan, Riau Islands is still low. This is suspected of having something to do with interpersonal communication and teacher work motivation. Therefore, it is necessary to conduct research to test its validity. This study aims to reveal thecontribution of interpersonal communication and work motivation to teacher job satisfactionn at SMKN Bintan Regency, Riau Islands. The hypotheses proposed in this study are: (1) interpersonal communication contributes to teacher job satisfaction, (2) work motivation contributes to teacher job satisfaction, (3) interpersonal communication and work motivation jointly contribute to teacher job satisfaction. The population in this study were all teachers of SMKN Bintan, Riau Islands, amounting to 135 people. The research sample amounted to 65 people who were taken by using stratified proportional random sampling technique. The research instrument used is a rating scale and a Likert Scale model questionnaire that has been tested for validity and reliability. The research data were analyzed by correlation and regression techniques. The results of data analysis show that: (1) Interpersonal communication contributes to teacher job satisfaction by 28.4%, (2) Work motivation contributes to teacher job satisfaction by 58.1%, (3) Interpersonal communication and work motivation together contribute to teacher job satisfaction by 70.3%. The achievement level of the teacher's job satisfaction score of 86.18% is in the satisfied category, and for interpersonal communication 82.47% is in the good category while for teacher work motivation 86.35 the ideal score is in the high category.